About 5–6 grades students preparation for participation in competitions and contests in mathematics - Sverdlova A. A. (Interactive science, 2019)
this article identifies and characterizes the pedagogical conditions for the organization of project activities in a modern primary school. In the analysis of scientific literature the author highlights the benefits of project activities, as well as the typical mistakes of teachers in the formation of project activities. The work also describes the pedagogical conditions.
Keywords: педагогические условия; проектная деятельность; мотивация; учащиеся; students; project activities; pedagogical conditions; motivation